On the oxidation behavior of titanium within coated nickel-based superalloys. (15th June 2015) - Bennett, R.J.; Krakow, R.; Eggeman, A.S.; Jones, C.N.; Murakami, H.; Rae, C.M.F.
Abstract: Rutile precipitation within alumina scales grown on coated nickel-based superalloy CMSX-4 has been found to occur preferentially at grain boundaries within the scale. Misorientation analysis using Rodrigues–Frank space has revealed clustering of the misorientation between neighboring grains of corundum and rutile about the established 〈0 0 0 1〉c 1 1 2 ¯ 0c //〈0 1 0〉r 1 0 1r orientation relationship observed in Ti-containing sapphire crystals. The fraction of interfaces found to exist in this configuration is sufficient to explain the nucleation of rutile from a single corundum grain abutting the rutile grain. The diffusive behavior of Ti has been observed to vary considerably within three commercially used coatings, a plain aluminide coating, a plat-aluminide coating and a diffused platinum coating. Titanium diffusion is enhanced by the presence of Pt. However this did not lead to the precipitation of more rutile, which although observed in all three coatings, was present in sufficient quantity to be detected using XRD only within the plain aluminide coated samples.